ETNOMATEMATIKA: IDENTIFIKASI UNSUR MATEMATIS PADA CANDI BRAHU - Anjariyah, Deka; Imanah, Ulil Nurul; Rahayu, Evi Kurnia; Susanto, Fran (Jurnal Penalaran dan Riset Matematika, 2025)
This study aims to describe the mathematical concepts embedded in the architectural structure of Brahu Temple in Mojokerto as a representation of local ethnomathematics. The research employs a qualitative approach with an ethnographic research design. Data collection techniques include literature review, field observation, and semi-structured interviews with site managers and local cultural figures. Data were analyzed using an interactive analysis model through stages of data reduction, data display, and conclusion drawing. The results reveal that Brahu Temple contains various mathematical elements, including circles and cylinders in the stupa-shaped roof structure, squares and rectangular prisms in the temple body, as well as squares and cuboids in the temple base. Additionally, elements of symmetry, reflection, trapezoids, and triangles are also found in ornamental patterns and structural details. These findings indicate that traditional temple architecture can serve as a rich source of learning that integrates mathematical concepts and local cultural values. Therefore, such cultural heritage can be effectively utilized in contextual mathematics learning to enhance students’ numeracy literacy and cultural awareness